ANALISIS INTERAKSI OBAT PADA PASIEN HIPERTENSI GERIATRI YANG MENJALANI RAWAT JALAN DI RS PKU MUHAMMADIYAH YOGYAKARTA AGUSTUS 2009-AGUSTUS 2010 - Dhanang Prawira Nugraha; Saepudin Saepudin; Joko Sudibyo (Khazanah: Jurnal Mahasiswa, 2016)
Increasing age can cause a variety of degenerative disease, one of which is hypertension. One issue is the treatment of geriatric polypharmacy the drug interactions may pose clinical problems that require a careful monitoring and action, for example the use of antihypertensives. This study aims to determine the picture of drug use and the relationship between the number of medication and comorbidities with potential drug interactions. This study is an observational analytic study using cross sectional study design. Data is retrospectively collected by using affordable population that meet the criteria. The determination of the relationship between the amount of active drug substance and the number of comorbidities, with the potential for drug interactions are analyzed using a linear regression. The results show that the most widely prescribed antihypertension research is in the singular (35.47%) of amlodipine (46.37%), about 51.27%) of the recipes contain a potential for drug interaction, with the potential drug inter actions at the level of the most significant (45.78%). The results of linear regression analysis showing the relationship between the amount of active drug sub stances and the number of potential drug interactions can be denoted by the equation y = 0.386 x- 0.385, but the relationship is very weak because of the pearson correlation (r) 0.491. The relationship between the number of comorbiditie and potential drug interactions can be denoted by the equation y = 0.416 x + 0.806, but the relationship is very weak because of the pearson correlation (r) 0.06.Key words: drug interaction, hypertension, geriatric, outpatient, PKU Muhammadiyah